Weak-value measurements can outperform conventional measurements. (19th December 2016) - Magaña-Loaiza, Omar S; Harris, Jérémie; Lundeen, Jeff S; Boyd, Robert W
Abstract: In this paper we provide a simple, straightforward example of a specific situation in which weak-value amplification (WVA) clearly outperforms conventional measurement in determining the angular orientation of an optical component. We also offer a perspective reconciling the views of some theorists, who claim WVA to be inherently sub-optimal for parameter estimation, with the perspective of the many experimentalists and theorists who have used the procedure to successfully access otherwise elusive phenomena.